2017
DOI: 10.1098/rspb.2016.2559
|View full text |Cite
|
Sign up to set email alerts
|

China's fight to halt tree cover loss

Abstract: China is investing immense resources for planting trees, totalling more than US$ 100 billion in the past decade alone. Every year, China reports more afforestation than the rest of the world combined. Here, we show that China's forest cover gains are highly definition-dependent. If the definition of ‘forest’ follows FAO criteria (including immature and temporarily unstocked areas), China has gained 434 000 km2 between 2000 and 2010. However, remotely detectable gains of vegetation that non-specialists would vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 30 publications
0
47
0
Order By: Relevance
“…Government statistics subsequently reported rapid increases in China's forest cover starting from the late 1990s (Figure ), although alternative assessments indicated that the increases were not as significant (Ahrends et al . ) or may even have been negative (China Nature Watch ). Regardless of the extent of increase, however, China's forests created via reforestation programs are overwhelmingly monocultures or compositionally simple forests (Xu ; Zhai et al .…”
Section: The Imperative Of Recovering China's Native Forestsmentioning
confidence: 99%
See 3 more Smart Citations
“…Government statistics subsequently reported rapid increases in China's forest cover starting from the late 1990s (Figure ), although alternative assessments indicated that the increases were not as significant (Ahrends et al . ) or may even have been negative (China Nature Watch ). Regardless of the extent of increase, however, China's forests created via reforestation programs are overwhelmingly monocultures or compositionally simple forests (Xu ; Zhai et al .…”
Section: The Imperative Of Recovering China's Native Forestsmentioning
confidence: 99%
“…Note that alternative assessments indicate that recent increases in China's forest cover are not as significant as government statistics suggest (Ahrends et al . ) or may even have been negative (China Nature Watch ).…”
Section: The Imperative Of Recovering China's Native Forestsmentioning
confidence: 99%
See 2 more Smart Citations
“…The choice of China as a location is appropriate given that it has conducted the largest afforestation programme of any country in an attempt to mitigate climate change. However, the devil is -as ever -in the detail, with the extent and quality of forest cover depending very much on definitions, and a considerable amount of afforestation occurring in areas that are of debateable suitability 3 . Something that could be of great benefit to effective tree-planting programmes is an improved understanding of the relationship between forest functions and biodiversity, and a study in this issue uses data from an Asian site to address such a question.…”
mentioning
confidence: 99%